Advanced Color Image Processing and Analysis - Fernandez-Maloigne, Christine; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
This volume does much more than survey modern advanced color processing. Starting with a historical perspective on ways we have classified color, it sets out the latest numerical techniques for analyzing and processing colors, the leading edge in our search to accurately record and print what we see. The human eye perceives only a fraction of available light wavelengths, yet we live in a multicolor world of myriad shining hues. Colors rich in metaphorical associations make us “purple with rage” or “green with envy” and cause us to “see red.” Defining colors has been the work of centuries, culminating in today’s complex mathematical coding that nonetheless remains a work in progress: only recently have we possessed the computing capacity to process the algebraic matrices that reproduce color more accurately. With chapters on dihedral color and image spectrometers, this book provides technicians and researchers with the knowledge they need to grasp the intricacies of today’s color imaging.
Fundamentals of Color -- CIECAM02 and its Recent Developments -- Color Difference Evaluation -- Cross-media Color Reproduction and Display Characterization -- Diherdral Color Filtering -- Color Representation and Processes with Clifford Algebra -- Image Super-resolution: A State-of-the-Art Review and Evaluation -- Color Image Segmentation -- Parametric Stochastic Modeling for Color Image Segmentation and Texture Characterization -- Color Invariants for Object Recognition -- Motion Estimation in Color Image Sequences -- Protection of Color Images by Selective Encryption -- Quality Assessment of Still Images -- Image Spectrometers, Color High Fidelity and Fine-art Paintings -- Application of Spectral Imaging to Electronic Endoscopes.
Keywords: Signal processing; Image processing; Speech processing systems; Optical data processing; Mathematics; Visualization; Signal, Image and Speech Processing; Computer Imaging, Vision, Pattern Recognition and Graphics; Visualization